Technical and economic feasibility of irrigated wheat as a function of nitrogen doses, sources, and inoculation with azospirillum brasilense - Galindo, Fernando Shintate [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Tarsitano, Maria Aparecida Anselmo [UNESP]; Buzetti, Salatiér [UNESP]; Santini, José Mateus Kondo; Ludkiewicz, Mariana Gaioto Ziolkowski [UNESP]; Alves, Cleiton José [UNESP] (Universidade Estadual de Londrina, 2018)
Azospirillum brasilense is a bacterium known for its biological nitrogen fixation (BNF) in wheat crops. However, there is a lack of comprehensive research defining how much mineral N should be applied to maximize the efficiency of BNF and attain high, economically sustainable yields. Moreover, it would be interesting to investigate whether adding urea with N- (n-butyl) thiophosphoric triamide (NBPT) urease inhibitor might increase BNF in grasses. The objective was to study the effect of inoculation with A. brasilense, associated with varying doses and sources of N, and economically evaluating the yield of irrigated wheat. The experiment was conducted in Selvíria – MS in crop years 2014 and 2015 in Oxisol soil type that was not-tilled. The experimental design was a randomized block with four replications, in a 2 × 5 × 2 factorial scheme, where 2 N sources (urea and Super N – urea with urease inhibitor enzyme), 5 nitrogen fertilization doses in top-dressing (0, 50, 100, 150, and 200 kg ha-1), were applied to wheat crops with or without the inoculation of A. brasilense. Our results showed that the supply of N through Super N was not economically superior to the use of conventional urea; therefore, we recommend the use of urea because of the ease of acquisition. The application of 140 kg ha-1 of N combined with inoculation with A. brasilense showed higher grain yield. However, the 50 kg ha-1 dose of urea in the absence of inoculation provided greater economic viability in wheat cultivation, but was not sufficient to ensure high profitability with grain productivity.
Keywords: Nitrogen fertilization; No tillage system; Total operational cost; Triticum aestivum